A cultural dictionary of punk : 1974-1982 - Rombes, Nicholas (Continuum, 2009)
"A Cultural Dictionary of Punk is organized around scores of distinct entries, on everything from Lester Bangs to The Slits, from Jimmy Carter to Minimalism, from 'Dot Dash' to Bad Brains."--Back cover